Bale Tani and Alang in the Perspective of Science, Local Wisdom and Community Religiosity â€œGumi Sasakâ€ Lombok (Preliminary Study in the Development of Science Learning Devices Based on Local Wisdom and Islamic Values) - Kurniawan Arizona; Gunawan; Ahmad Harjono; Joni Rokhmat; Agus Ramdani; AA Sukarso (Postgraduate, University of Mataram, 2023)
The existence of